IMPLEMENTASI WAWASAN EKONOMI SYARI'AH PADA KEGIATAN EKONOMI MAHASISWA - Reza Hilmy Luayyin; Muhammad Alfi Syahrin; Tuhfatul Janan; Agniz Ruri Ambarwati (LPPM STAI Muhammadiyah Probolinggo, 2022)
Each student has different level of understanding. Most of them have different knowledge, especially in mastering science of sharia economics. Sharia economics is very different, of course, from conventional economics. A lot of them better understand or are more familiar with conventional-based economic terms. Sharia economics or the study of mu'amalah still feels unusual to them. The problems that occur to students STAI Muhammadiyah Probolinggo show that there are differences in attitudes and behavior in implementing sharia economic activities with mastery of sharia economic material in class. This study examines extent of insight and mastery of sharia economics in sharia economics students in each of their economic activities. This study uses a qualitative descriptive method, which is a method that aims to describe the nature of something that is ongoing in time the research conducted and examines the causes of a symptom. The data collection technique obtained by the author is through observation and interview techniques. This research data obtained from the first semester of Islamic economics students. The results showed that students had a high enthusiasm and curiosity in learning and mastering economics, eager to try something new, especially in the field of Islamic economics, most of them wanted to carry out more Islamic economic activities, although some still use Islamic economics, conventional, wants to be more active and learn deeper about sharia economic norms, values, and principles has good economic insight because they understand that conventional banks considered to have a threat of usury in them even though they are still selected, have insight and knowledge about Sharia economics and able to apply it in their daily activities, They still not mastered Islamic economics related to more technical matters, such as analyzing business risk and business management. Meanwhile, the students' implementation of sharia economic insight that carried out by students is going well, it can be seen from the variety of sharia-based business, inviting the closest family to do business of sharia-based and starting to carry out activities in sharia banking. Students are also able to show the implementation of basic insights and understanding of high sharia economics because they are able to refrain from spending wealth just for pleasure but the orientation is for their own benefit.